The Effect of Health Promotion through Video Media on HIV/AIDS Stigma among Adolescents - Haris, Nursani A; Astuti, Dhesi Ari (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: HIV/AIDS is both a health and social issue, as its spread is heavily influenced by people's behaviors and knowledge. According to WHO data from 2022, 20 million adolescent females and 17.4 million adolescent males were infected with HIV. Meanwhile, data from the Indonesian Ministry of Health (Kemenkes RI) in 2022 reported that 741 adolescents were diagnosed with HIV. In its efforts to combat HIV/AIDS, the Indonesian Ministry of Health is committed to achieving the "3 Zeroes" targets: zero new HIV infections, zero stigma and discrimination, and zero AIDS-related deaths. Video serves as a medium for delivering information and messages, which focuses on promoting health programs by prioritizing education, engaging health information, and effective communication. Aims: This study aims to investigate the effect of health promotion using video media on HIV/AIDS stigma among adolescents. Method: This study employed quantitative method with pre-experimental design. The sample consisted of 38 respondents selected through purposive sampling. A video about HIV/AIDS and a questionnaire were used as instruments. This study utilized a one-group pretest-posttest design with the Wilcoxon statistical test. Result: The results showed that health promotion through video media had a significant effect on reducing HIV/AIDS stigma among adolescents. The p-value is 0.000 < 0.05, which indicated that the (Ho) was rejected, and the (Ha) was accepted. Conclusion: There was a reduction in stigma following the health promotion using video media.